The Impact of Discovery Learning Model with Lumio by SMART on High School Students' Engagement and Learning Outcomes in Static Fluids - Choir, Ridha Amalila; Maryani, Maryani; Ernasari, Ernasari (Universitas Islam Negeri (UIN) Mataram, 2024)
This study examines the impact of the Discovery Learning model assisted by Lumio by SMART on high school students' learning activities and outcomes in a static fluid material, which is difficult to understand without experiments. Discovery Learning encourages students to discover concepts independently, enhancing comprehension and retention, while Lumio provides interactive media, such as simulations and animations, to support active learning. This experimental research used a post-test-only control group design with a randomly selected sample from 142 students in grade XI science. Data were collected through multiple-choice tests, observations, interviews, and documentation and analyzed using normality tests and statistical tests with SPSS V25. Results showed that the experimental class had higher learning activity (83.571) than the control class (69.028), with an independent sample T-test yielding a significance value of 0.000 ≤ 0.05. Learning outcomes were also higher in the experimental class (83.43) than in the control class (68.33), analyzed using the Mann-Whitney U-Test due to non-normal data distribution, with a significance value of 0.000 ≤ 0.05. These findings indicate that the Discovery Learning model assisted by Lumio by SMART positively affects students' learning activities and outcomes, suggesting its potential integration with other interactive media or learning models for future research.